Panorama do mercado atual de insumos farmacêuticos no Brasil. - MALENGO, Luiz de Jesus (129, 2024)
Neste artigo será apresentado as características do mercado nacional e internacional de Insumos Farmacêuticos Ativos, mostrando as dificuldades do mercado nacional na produção de insumos e a dinâmica economia no setor farmacêutico criada pelas políticas governamentais a partir da abertura econômica no ano de 1990. As estruturas das patentes no setor farmacêutico, uma discussão das influências do setor farmacêutico político e econômico nos aspectos sociais no Brasil e por último uma alternativa de produção de IFAs no Brasil usando a matéria-prima orgânica como alternativa de produção para amenizar e diminuir a dependência do mercado internacional na importação de insumos.

Abstract: This article will present the characteristics of the national and international markets, highlighting the challenges faced by the domestic market for the production of inputs and the economic dynamics in the pharmaceutical sector created by government policies following the economic opening to the international market in 1990. It will also cover the patent structures in the pharmaceutical sector, a discussion of the political and economic influences of the pharmaceutical sector on social aspects in Brazil, and finally, an alternative for the production of Active Pharmaceutical Ingredients (APIs) in Brazil using organic raw materials as a production alternative to alleviate and reduce dependence on international markets for input imports.
Overview of the current pharmaceutical inputs market in Brazil.
Keywords: Insumos farmacêuticos; Patente; Gestão e Negócios